Influences of soil properties and long-time aging on phytotoxicity of antimony to barley root elongation. (July 2020) - Lin, Xianglong; He, Fei; Sun, Zaijin; Hou, Hong; Zhao, Long
Abstract: Antimony (Sb) is a toxic element of global concern. To date, the most previous researches about phytotoxicity of Sb failed to fully consider the effects of soil properties and long-time aging. To address this, the toxicity of exogenous Sb(III) and Sb(V) were studied using the standardized barley root elongation bioassay. The results indicated that in ten soils aged only for 1 d, the EC10 (concentrations causing 10% inhibition) values were 221–3164 mg kg −1 and 135–4260 mg kg −1 in Sb(III)- and Sb(V)-treated soils, respectively. The EC50 values (concentrations causing 50% inhibition) were more than the setting highest concentration of 6400 mg kg −1 in half of ten soils. The regression analysis showed that the amorphous Fe oxide and pH were the most foremost single soil factor explaining above-mentioned variance in EC10, respectively, which suggested that the dominant soil factors were related to Sb forms. The inclusion of amorphous Mn oxide in above these two simple regression model could best explain the toxicity variance. After aged for 116 and 365 d, the phytotoxicity of Sb in Sb-treated soils significantly decreased and the phytotoxicity were even not found in the majority of Sb(V)-treated soils. The extent of aging varied with soils, and correlation analysis indicated that the aging effects negatively correlated with soil pH and positively correlated with clay and amorphous Al oxide in the Sb(III)-treated test soils. Graphical abstract: Image 1 Highlights: Amorphous Fe oxide and pH were dominant single factor in Sb(III)- and Sb(V)-treated soils, respectively. Sb(V) exhibited no toxicity after aged for 365 d in the most soils. Aging effects on Sb(III) negatively correlated with pH and positively correlated with clay and amorphous Al oxides. Abstract : The most important soil factors influencing Sb phytotoxicity related to Sb forms added into soil, and the different aging effects on phytotoxicity of Sb in different soils were observed.